2022
DOI: 10.3390/molecules28010307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiprotozoal Activity of Azabicyclo-Nonane Pyrimidine Hybrids

Abstract: 2,4-Diaminopyrimidines and (dialkylamino)azabicyclo-nonanes possess activity against protozoan parasites. A series of fused hybrids were synthesized and tested in vitro against pathogens of malaria tropica and sleeping sickness. The activities and selectivities of compounds strongly depended on the substitution pattern of both ring systems as well as on the position of the nitrogen atom in the bicycles. The most promising hybrids of 3-azabicyclo-nonane with 2-aminopyrimidine showed activity against P. falcipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The findings demonstrated that doxorubicin displayed IC 50 values ranging from 1. 25 The cytotoxicity observation suggests that BV2 and HAPI cell lines possessed more cell viability in the presence of the test molecules compared with N9 and HMO6 cells and were selected for further investigation.…”
Section: Screening Of Synthesized Compounds For Cellular Toxicity Aga...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings demonstrated that doxorubicin displayed IC 50 values ranging from 1. 25 The cytotoxicity observation suggests that BV2 and HAPI cell lines possessed more cell viability in the presence of the test molecules compared with N9 and HMO6 cells and were selected for further investigation.…”
Section: Screening Of Synthesized Compounds For Cellular Toxicity Aga...mentioning
confidence: 99%
“…[4] Molecular hybrids are a promising area for research in medicinal chemistry as they incorporate different scaffolds into one molecule, improving their affinity and efficacy. [5][6][7] These hybrids have exhibited multifarious actions, including anticancer, [8][9][10][11][12][13][14][15][16][17] antimicrobial, [18,19] antiinflammatory, [20,21] anti-diabetic, [22][23][24] and antiprotozoal activities, [25][26][27] owing to their diverse pharmacophore characteristics. Molecular hybrids with furan, pyrazole, and thiazolidinedione moieties have recently gained significant attention.…”
Section: Introductionmentioning
confidence: 99%